Evaluation of formation damage caused by drilling fluid in deviated wellbore - Md Yassin, Abu Azam; Ismail, Abdul Razak; Mohammad, Abd. Halim (Jawatankuasa Penyelidikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1993)
Wellbore damage shape around inclined an horizontal wells are commonly assumed as radial. This is conceptual assumption. A more realistic model was investigated experimentally in this study, since the distribution of damage surrounding an inclined or horizontal well that determines its shapes are not only influenced the anisotropy of formation rocks but are also strongly influenced by borehole angles and the dynamic of filtration process in drilling. A novel, state-of-the-art engineering core flow tests set up was constructed using long cores which permit in-situ determination of permeability profile as a function of core length. Results from these tests on 5 core sample locations around an inclined wellbore shows that the severity of damage is reduced slighty from the upper side to the lower side around the inclined vvellbore wall. Analysis on degree of damage permeability distribution around the inclined wellbore indicated that the damage shape is elliptical.